Thrombolysis of basilar artery occlusion: Impact of baseline ischemia and time. Issue 6 (8th July 2013) - Strbian, Daniel; Sairanen, Tiina; Silvennoinen, Heli; Salonen, Oili; Kaste, Markku; Lindsberg, Perttu J.
<x xml:space="preserve">Abstract</x> Objective To evaluate the impact of extensive baseline ischemic changes on functional outcome after thrombolysis of basilar artery occlusion (BAO), and to study the effect of time to treatment in the absence of such findings. Methods We prospectively evaluated 184 consecutive patients with angiography‐proven BAO. The majority of patients received intravenous alteplase and concomitant full‐dose heparin. Extensive baseline ischemia was defined as posterior circulation Acute Stroke Prognosis Early CT score (pc‐ASPECTS) < 8. Onset‐to‐treatment time (OTT) was evaluated both as a continuous and as a categorical variable (0–6 hours, 6–12 hours, 12–24 hours, and 24–48 hours). Successful recanalization means thrombolysis in myocardial infarction (TIMI) = 2 to 3. Symptomatic intracranial hemorrhage (sICH) was evaluated with National Institute of Neurological Disorders and Stroke, European Cooperative Acute Stroke Study II, and Safe Implementation of Thrombolysis in Stroke criteria. Poor 3‐month outcome was defined as modified Rankin Scale score of 3 to 6. Results The majority (96%) of patients with baseline pc‐ASPECTS < 8 had poor 3‐month outcome, and a similar number (94%) was observed in those of them with confirmed recanalization (51.5%). In contrast, half of the patients with pc‐ASPECTS ≥ 8 and successful recanalization (73.2%) achieved good outcome. In these patients, OTT was associated with poor outcome neither as a continuous nor as a categorical variable. Factors independently associated with poor outcome were greater age and baseline National Institutes of Health Stroke Scale, lack of recanalization, history of atrial fibrillation, and sICH. In the model including the whole cohort (patients with any pc‐ASPECTS), pc‐ASPECTS < 8 was independently associated with poor outcome (odds ratio = 5.83, 95% confidence interval = 1.09–31.07). Interpretation In the absence of extensive baseline ischemia, recanalization of BAO up to 48 hours was seldom futile and produced good outcomes in 50% of patients, which was independent of time to treatment. ANN NEUROL 2013;73:688–694